Efektifitas Sistem Rekrutmen Guru Pendidikan Formal Yayasan Pondok Pesantren Darussalam Blokagung Karangdoro Tegalsari Banyuwangi Tahun Pembelajaran 2018/2019 - Budiywono, Eko; Annas, Muhamad; Aliya, Mahya (Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2019)
The objectives in this study are: (1) Knowing the formal education recruitment system; (2) Knowing the supporting and inhibiting factors in it; (3) Knowing the right strategy to be applied to the formal education teacher recruitment system which is located at the Darussalam Block Pondok pesantren foundation in the 2018/2019 Academic Year. This research method uses descriptive qualitative, data collection through interviews, observation, and documentation. Data analysis using SWOT analysis and data validity techniques using triangulation. The results of his research, the effectiveness of the formal education teacher recruitment system at the Darussalam Blockagung boarding school foundation include: (1) Teacher recruitment prioritizes students and alumni of the foundation as educators who fit the vision and mission of the foundation (2) Teacher recruitment is carried out centrally by the head of education and teaching (3) Submission of a temporary teacher decision letter for 2 years as a test of teacher loyalty at the foundation.